2009
DOI: 10.1111/j.1365-2265.2008.03374.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on A‐FABP, lipocalin‐2 and RBP4 levels in obese women

Abstract: Exercise training with weight loss induced a significant reduction in circulating A-FABP levels in obese Korean women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
89
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 28 publications
12
89
4
Order By: Relevance
“…Choi et al found that lipocalin-2 concentrations did not differ between obese and normal weight women. Exercise training and weight loss did not affect lipocalin-2 or the well-established inflammatory marker hs-CRP [27]. Due to its autocrine or paracrine effects, lipocalin-2 antagonised the inflammatory effects of TNF-a in macrophages [8,14].…”
Section: Prace Oryginalnementioning
confidence: 90%
“…Choi et al found that lipocalin-2 concentrations did not differ between obese and normal weight women. Exercise training and weight loss did not affect lipocalin-2 or the well-established inflammatory marker hs-CRP [27]. Due to its autocrine or paracrine effects, lipocalin-2 antagonised the inflammatory effects of TNF-a in macrophages [8,14].…”
Section: Prace Oryginalnementioning
confidence: 90%
“…One study using visceral fat from obese subjects did confirm lipocalin 2 mRNA expression in this tissue, but subcutaneous fat tissue was not studied (10). Interventional studies looking at the effect of weight loss, which is known to improve insulin sensitivity, have mostly found no change in lipocalin 2 levels with weight loss (18,19), although a recent study did find a reduction in women with polycystic ovary syndrome (PCOS) (20). Despite the significant correlation between lipocalin 2 and HOMA-IR at baseline when adjusting for anthropometric measurements, this correlation disappears after also adjusting for serum creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…Interventional studies on circulating AFABP Several interventional studies have evaluated the influence of weight reduction and statin use on circulating AFABP (Table 3). All [81][82][83] except one [84] published studies have demonstrated that the serum AFABP level is reduced following successful weight reduction through lifestyle or surgical measures. Furthermore, atorvastatin treatment over 3 months has been found to significantly decrease circulating AFABP levels in statin-naive participants with atherosclerosis [85], in agreement with in vitro findings [57].…”
Section: Controlsmentioning
confidence: 99%